Reviews of new publications - Holmes, Derek A (KUKILA, 1987)
Chalmers, M.L. 1986. Annotated checklist of the birds of Hongkong, fourth edition. Hongkong Bird Hatching Society.White, C.M.N. 6 M.D. Bruce. 1986. The Birds of Wallacea (Sulawesi, The Moluccas & Lesser Sunda Islands, Indonesia). An annotated checklist. Brit. Orn. Union Checklist 7.Beehler, B.M., Pratt, T.K. S D.A. Zierman. 1986. Birds of New Guinea. Handbook no. 9. Wau Ecology Institute, Papua New Guinea. Princeton University Press.